CONTRAST ASSOCIATED NEPHROPATHY AFTER INTRAVENOUS ADMINISTRATION: HOW TO ACESS CHRONIC KIDNEY DISEASE? (International conference on multidisciplinary science, 2025)
Chronic kidney injury in the setting of contrast medium (CM) administration has been extensively studied after it was first described in 1954 [1]. Since then, significant research has been devoted to the recognition, diagnosis,and prevention of this entity. Most of the earlier studies have focused on the consequences of intraarterial (IA) CM administration in general and cardiac angiography in parti-cular. It was not until 1985 that researchers analyzed the renal function of patients after CM-enhanced computed-tomography (CT) scans.